Improving Students’ Scientific Literacy through Distance Learning with Augmented Reality-Based Multimedia Amid the Covid-19 Pandemic (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Scientific literacy is a capability to identify problems, analyze questions, and create solutions by applying scientific knowledge and integrating science with technology and society. This literacy needs to be improved so that students can develop their skills in identifying science phenomenon and addressing various solutions. Although the learning was conducted in distance since the current situation is still amid the COVID-19 pandemic, the literacy can be taught during the learning process. This study aims to improve students’ scientific literacy through distance learning with augmented reality-based multimedia amid the COVID-19 pandemic. The research included in a descriptive quantitative study with pre-test and post-test design. The distance learning was conducted in the lecture of anatomy and physiology of organism during even semester in May 2020, with 111 students from three classes in the 2018 academic year. The science content provided in online learning was supported by augmented-reality based multimedia on the topic of the human respiratory system. This multimedia was evaluated, also stated as valid and appropriate to be implemented in the learning process. Scientific literacy was measured using the online test form. The findings indicated that the students’ scientific literacy improved moderately both in class A and B, but low in class C. The improvement of scientific literacy in class A reached N-gain average score of 0.31, class B reached 0.38, and class C reached 0.22. Students also gave a positive response, showed by the percentages of students’ response at 89.1% in class A, 87.0% in class B, and 84.8% in class C, which was in the very strong category. Therefore, it can be concluded that students’ scientific literacy improved well through distance learning with augmented reality-based multimedia amid the COVID-19 pandemic.